Reakcje w Gruzji na wybuch powstania styczniowego - Adamczewski, Przemysław (1981– ); Kiknaje, Važa (1952– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article presents the response that news of the January Uprising in the Kingdom of Poland provoked in Georgia. In this context, the news about the uprising that appeared in the official press, presenting the government’s position, as well as the news published in magazines issued by the Georgian intellectual elite, were discussed. In addition, archival testimonies were cited showing that money was collected in Tiflis for the benefit of the insurgents, which was to be handed over to their representative in Odesa.
p. 5-28
Summary in English and Russian.
Keywords: Poland; Georgia; Georgia (Republic); January Uprising; Poland - 1863-1864 (January Uprising); magazine "Sakartvelos Moambe"; newspaper "Kavkaz"